English Language Learning Skill and The Relationship To Academic Achievement Among Primary School Students - Mohamed Habib Yahiaoui; Ahlem Bouaroua (Journal of Science and Knowledge Horizons, 2025)
The current study aims to explore the relationship between english language learning skills and academic achievement among primary school students. The study sample consisted of 150 students from various primay schools in the chlef province. The descriptive method was used, along with a questionnaire on english language learning skilsl prepared by the researchers after ensuring its psychometric properties. The data was prossed using appropriate statistical methods, leading to the following results : the most common english language learning skills among primary school students include: motivation and rediness, listning comprehension , speaking, and writin.  there is no satistically significant relaionship between english language learning skills and academic achievement among primary school students. There are no statistically significant differences in english language learning skills based on gender (male, female) among primary school students.